NK Cell Development in Times of Innate Lymphoid Cell Diversity - Stokic-Trtica, Vladislava; Diefenbach, Andreas; Klose, Christoph S. N. (Frontiers in Immunology, 2020)
After being described in the 70s of the last century as cytotoxic cells that do not require pre-activation, natural killer (NK) cells remained the sole member of innate lymphocytes for decades until lymphoid-tissue inducer cells in the 1990s and helper-like innate lymphoid lineages from 2008 on completed the picture of innate lymphoid cell (ILC) diversity. Since some of the ILC members, such as ILC1s and CCR6- ILC3s share specific markers previously used to identify NK cells, these findings provoked the question on how to delineate development of NK cell and helper-like ILCs and how to properly identify and genetically interfere with NK cells. The description of Eomesodermin (Eomes) as lineage-specifying transcription factor of NK cells provided a candidate that may serve as a selective marker for the genetic targeting and identification of NK cells. Unlike helper-like ILCs, NK cell activation is to a large degree regulated by engagement of activating and inhibitory surfaces receptors. NK cell research has revealed some elegant mechanisms of immunosurveillance coined “missing-self” and “induced-self” recognition, thus complementing “nonself recognition” predominantly utilized by adaptive lymphocytes and myeloid cells. Notably, the balance of activating and inhibitory signals perceived by surface receptors can be therapeutically harnessed for anti-tumor immunity mediated by NK cells. This review aims to summarize similarities and differences in development, function, localization and phenotype of NK cells and helper-like ILCs, with the purpose to highlight unique feature of NK cell development and regulation.